Solid–liquid equilibria, physicochemical and microstructural studies of binary organic eutectic alloy: urea + 2-aminobenzothiazole system - Sharma, Krishna Prasad; Shakya, Pawan Raj; Rai, Ramananda (Scientific World, 2012)
Phase diagram of binary organic system of urea (U) with 2-aminobenzothiazole (ABT) shows the formation of a eutectic at 0.350 mole fraction of urea. Growth kinetics of the eutectic and pure components studied by measuring the rate of movement of solid-liquid interface in a thin glass U-tube at different undercoolings (ÄT) suggests the applicability of HilligTurnbull’s equation: v = u (ÄT) n. The thermodynamic functions such as heat of mixing, entropy of fusion, roughness parameter, interfacial energy and excess thermodynamic functions were calculated from the enthalpy of fusion values, obtained from DSC data. The optical microphotographs of pure and eutectic alloy show their characteristic features. Scientific World, Vol. 10, No. 10, July 2012 p91-94 DOI: http://dx.doi.org/10.3126/sw.v10i10.6871